Design and Photocatalytic Activity of Mesoporous TiO/ZrO Thin Films - Yu. Gnatyuk; N. Smirnova; A. Eremenko; V. Ilyin (Adsorption Science & Technology)
Optically transparent, crack-free mesoporous titania and zirconia-doped titania thin films were fabricated by the sol—gel technique using the non-ionic amphiphilic triblock copolymer Pluronic P123 as the template. The structure and optical properties of these films were characterized using TEM, low-angle XRD, DTA/TG measurements, UV—vis spectroscopy and hexane adsorption investigations. It was found that addition of ZrO 2 into the TiO 2 matrix retarded sintering of the films, thereby increasing the specific surface area after treatment up to 500°C. The catalytic activity of the mesoporous TiO 2 and TiO 2 /(5–30%) ZrO 2 films in ethanol photo-oxidation increased with increasing specific surface area and surface acidity of the samples.